The effect of amine substituent chain length on POSS/Polysulfone mixed matrix membrane - Bong, Y.C. (Universiti Malaysia Pahang, 2018)
The main obstacle encountered during the development of polyhedral oligomeric silsesquioxane (POSS) mixed matrix membrane (MMM) via physical blending is the combination of compatible inorganic filler and polymeric matrix. In this work, mono-functional POSS of different amine functionalised substituent chain lengths namely aminopropylisobutyl POSS (AMPOSS-a) and aminoethylaminopropylisobutyl POSS (AMPOSS-b) were incorporated into Polysulfone (PSf) membrane at 1wt, 2wt and 3wt loadings. The effect of amine substituent chain lengths on its compatibility and dispersion properties as well as the glass transition temperature of the MMMs were studied using scanning electron microscope (SEM), energy dispersive X-ray (EDX) and differential scanning calorimeter (DSC). Particle agglomerations were observed to increase with the loadings of both fillers although more prominent in AMPOSS-b/PSf membranes. This was attributed to the interparticle forces such as van der Waals and electrostatic forces. Distribution of both fillers were concentrated at the upper region of the membranes at 1wt and 2wt as a consequence of their density difference. The glass transition temperature (Tg) for pristine PSf at 197ºC showed an overall decrement between 40.3ºC to 47.1ºC when AMPOSS-a and AMPOSS-b were incorporated. The decrement was due to AMPOSS particle loadings, surface chemistry and particle-polymer chain topology. Hence, mono-substituted POSS with varying amine substituent chain lengths did not improve the glass transition temperature nor contribute to homogeneous MMM morphology. This had been identified to be the consequence of POSS surface energy, which might be caused by the association of hydrocarbon chains saturated on the particle surface due to the presence of isobutyl group. © Universiti Malaysia Pahang, Malaysia